How do families respond to a crisis? The experience of sexual trafficking victim families - Herdiana, Ike (Universitas Mercu Buana Yogyakarta, 2024)
A family crisis refers to the incapability or disorganization of a family due to resource scarcity and negative perception of stressors. This study aims to describe familial responses to a crisis, particularly in the context of sexual trafficking. A qualitative method was used with an instrumental case study approach. Participants were five family members of sexual trafficking victims in East Java, Indonesia. Data were collected from semi-structured interviews to allow in-depth inquiries and then analyzed using a bottom-up thematic analysis. Data source triangulation, theory triangulation, and member-checking were conducted to support the convergence of the data. The results depicted psychological, physiological, social, and relational strains as familial responses to sexual trafficking. The study recommends future research to, first, explore resources that can contribute to building resilient families, and second, develop family-based interventions for professionals dealing with trafficking victims. Keywords:Sexual trafficking victims; experience of families; crisis.